2014
DOI: 10.1007/s13659-014-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Assessment of Cadinene Sesquiterpenes from Eupatorium adenophorum in Mice

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Pesticides or medicine products must pass a safety evaluation and clinic trials before being approved for public use. In our previous research, we found a significant increase (P<0.01) and decrease (P<0.01) of the spleen index and thymus index with the treatment of DAOA (Ouyang et al 2015). The reduction of the spleen resulted from lowered immune function of the cells, and the severe thymic atrophy resulted from the toxic action of immune system from drugs.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Pesticides or medicine products must pass a safety evaluation and clinic trials before being approved for public use. In our previous research, we found a significant increase (P<0.01) and decrease (P<0.01) of the spleen index and thymus index with the treatment of DAOA (Ouyang et al 2015). The reduction of the spleen resulted from lowered immune function of the cells, and the severe thymic atrophy resulted from the toxic action of immune system from drugs.…”
Section: Discussionmentioning
confidence: 84%
“…The histopathological images of the spleen and thymus were proof of immunologic function damage. In addition, lymphocyte (LYM) count, red blood cell (RBC) count, and hemoglobin content (HGB) in serum also exhibited significant decreases (P<0.01) on treatment of 300 mg kg −1 BW DAOA and OA (Ouyang et al 2015), which may be mediated by effects associated with the plasma membrane, interference or cellular metabolic pathways. Therefore, any dose that poses a potential risk to the immune system must be larger than 150 mg kg −1 BW of DAOA and OA.…”
Section: -B C 3-b and C)mentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Euptox A has been found to show hepatotoxicity in rats 19 and immunotoxicity in mice. 6 Therefore, in this study, we aimed to explore the mechanisms underlying the effects of Euptox A on mouse splenocytes. Cell cycle control is a major regulatory mechanism in the process of cell growth, and many cytotoxic substances cause cell death by cell cycle arrest at the G0/ G1, S, or G2/M phases.…”
Section: Discussionmentioning
confidence: 99%